2013
DOI: 10.1111/mmi.12282
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of fatty acid biosynthesis in mycobacteria

Abstract: SUMMARY The main purpose of our study is to understand how mycobacteria exert control over the biosynthesis of their membrane lipids and find out the key components of the regulatory network that control fatty acid biosynthesis at the transcriptional level. In this paper we describe the identification and purification of FasR, a transcriptional regulator from Mycobacterium sp. that controls the expression of the fatty acid synthase (fas) and the 4-phosphopantetheinyl transferase (acpS) encoding genes, whose pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 62 publications
1
62
0
Order By: Relevance
“…1), a tunnel that is conspicuously opened on both ends. This singular solution has evolved to lodge the kind of acylated chains of 20 and more carbons that inhibit FasR binding to its cognate DNA (7).…”
Section: The Singular Tunnel In Fasr Is Predicted To Accommodate Verymentioning
confidence: 99%
“…1), a tunnel that is conspicuously opened on both ends. This singular solution has evolved to lodge the kind of acylated chains of 20 and more carbons that inhibit FasR binding to its cognate DNA (7).…”
Section: The Singular Tunnel In Fasr Is Predicted To Accommodate Verymentioning
confidence: 99%
“…A few transcription regulators that directly regulate the biosynthesis genes have been identified. FasR regulates the expression of the fas gene (15), while MabR (16) and FadR (17) regulate the expression of the fabD-accD6 cluster, the fasII operon (Fig. 1B).…”
mentioning
confidence: 99%
“…Our laboratory is actively studying lipid metabolism in mycobacteria and related actinomycetes (RodrĂ­guez et al 2001; Gago et al 2006; Kurth et al 2009; Salzman et al 2010; Mondino et al 2013; Comba et al 2014; Menendez-Bravo et al 2014; Bazet Lyonnet et al 2014). The structure and biosynthesis of the unique fatty acids found in the complex lipids that form the M. tuberculosis cell envelope has been the subject of intense research efforts (DaffĂ© 2008), primarily because the enzymes involved in their metabolism offer attractive and selective targets for the development of antimycobacterial drugs or for their use in biotechnological processes (Zhang 2005; Menendez-Bravo et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from participating in numerous metabolic pathways as substrates and intermediates (Haynes 2011), CoA and a number of its thioester derivatives, such as acetyl-CoA, can also regulate directly the activity of proteins by allosteric mechanisms and by affecting protein acetylation reactions (Shi and Tu 2015). It has also been found that CoA-thioesters have the ability to regulate gene expression by modulating the affinity of transcription factors for their target DNA (Black et al 2000; Mondino et al 2013). …”
Section: Introductionmentioning
confidence: 99%